MAGs-based genomic comparison of gut significantly enriched microbes in obese individuals pre- and post-bariatric surgery across diverse locations - Shi, Hang; Li, Jia (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionObesity, a pressing global health issue, is intricately associated with distinct gut microbiota profiles. Bariatric surgeries, such as Laparoscopic Sleeve Gastrectomy (LSG), Sleeve Gastrectomy (SG), and Roux-en-Y Gastric Bypass (RYGB), induce substantial weight loss and reshape gut microbiota composition and functionality, yet their comparative impacts remain underexplored.MethodsThis study integrated four published metagenomic datasets, encompassing 500 samples, and employed a unified bioinformatics workflow for analysis. We assessed gut microbiota α-diversity, identified species biomarkers using three differential analysis approaches, and constructed high-quality Metagenome-Assembled Genomes (MAGs). Comparative genomic, functional profiling and KEGG pathway analyses were performed, alongside estimation of microbial growth rates via Peak-to-Trough Ratios (PTRs).ResultsRYGB exhibited the most pronounced enhancement of gut microbiota α-diversity compared to LSG and SG. Cross-cohort analysis identified 39 species biomarkers: 27 enriched in the non-obesity group (NonOB_Enrich) and 12 in the obesity group (OB_Enrich). Among the MAGs, 177 were NonOB_Enrich and 14 were OB_Enrich. NonOB_Enrich MAGs displayed enriched carbohydrate degradation profiles (e.g., GH105, GH2, GH23, GH43, and GT0 families) and higher gene diversity in fatty acid biosynthesis and secondary metabolite pathways, alongside significant enrichment in amino acid metabolism (KEGG analysis). Post-surgery, Akkermansia muciniphila and Bacteroides uniformis showed elevated growth rates based on PTRs.DiscussionThese findings underscore RYGB’s superior impact on gut microbiota diversity and highlight distinct microbial functional adaptations linked to weight loss, offering insights for targeted therapeutic strategies.